Social power and the Turkish state - Jacoby, Tim, 1969- (Frank Cass, 2004)
This book uses the historical sociological approach of Michael Mann to analyse the process of state-building in Turkey from the changes developed during the Ottoman Empire to the organisation of the modern-day government.